Equatorial Guinea : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2003)
The discussions for the 2003 Article IV Consultation with Equatorial Guinea were conducted in Malabo and Bata. Executive Directors expressed concern about the continued weakness in economic policy performance, macroeconomic management, and governance. The authorities agreed that Equatorial Guinea's medium-term economic outlook was favorable, provided that sound economic management was put in place and maintained. The macroeconomic stability needed to be complemented by a number of structural reforms to foster non-oil growth. The recently established government-owned oil company (GEPETROL) has initiated some operations.